Addressing Cybercrime Against Women: A Digital Threat of Growing Concern in India - Sumanth S. Hiremath (Randwick International of Social Science Journal, 2025)
The rapid growth of the internet has led to a significant increase in cybercrimes, with women being disproportionately affected. Cyber Violence against Women and Girls (CVAWG) is an increasing concern around the world. Since the age of 15, one in ten women has been the victim of cybercrime. Women in India deal with unique challenges, such as online harassment, stalking, revenge porn, etc. These things have serious effects on their overall health. To find out what causes cybercrime and make the internet safer for women, it is necessary to look at it from a sociological perspective. This means recognising women's freedom and voices online and working to make the internet a more welcoming and empowering place. To effectively address such issues, the Indian Penal Code (IPC) and the Information Technology (IT) Act need to be made more stringent. In addition, knowing how to use computers and the internet is very important for stopping cybercrimes.